Performance of Resource Efficient Routing Protocols for ireless Ad-hoc Networks in the Presence of Channel Fading - Sheikh, A.U.H.Khan (2006)
Adhoc networks interconnect mobile terminals without intervention of a base station in other words these networks do not use traditional infrastructure of base stations to interconnect to complete a communication link. In these networks, the mobile units operate in store and forward mode until the data reaches the destination. Due to mobility of the participating nodes, the network configuration continuously changes and the currently route in use may not be available. This necessitates establishing a new route. This paper compares the network throughput for several protocols from the point of view of resource efficiency when the channel fading is present.